The role of current product release criteria for identification of human islet preparations suitable for clinical transplantation. - Eckhard, M; Brandhorst, D; Winter, D; Jaeger, C; Jahr, H; Bretzel, R; Brendel, MD (2004)
BACKGROUND: Alloimmunity, autoimmunity, and nonspecific inflammation are known to be potential determinants for long-term islet survival and insulin independence. Sufficient islet mass is a key determinant. But islet engraftment and posttransplant survival may also depend on functional characteristics of the graft. This study investigated the significance of current product release criteria for the transplantation outcome. METHODS: Fourty five consecutive transplanted human islet preparations and their functional outcomes were analyzed. Islet mass was determined according to standard criteria: purity by light microscopy, viability by dye exclusion and Insulin secretory response to static glucose incubation. Islet graft function was monitored for > or = 1 year. Islet function was defined as full (FF), partial (PF), or nonfunction (NF) based on serum C-peptide levels and insulin independence. RESULTS: All islet grafts displayed primary function. Islet mass [IEQ/kg BW]: 7331.3 +/- 679.7 (FF), 5821.3 +/- 546.7 (PF), 6468.6 +/- 658.5 (NF), (FF vs PF p = .032) Purity [%] 86.9 +/- 3.1 (FF), 76.0 +/- 2.87 (PF), 88.2 +/- 2.3 (NF) (FF vs PF P =.045, PF vs NF, P = 0.01). (4) Viability [%]:89.2 +/- 2 (FF), 86.2 +/- 1.7 (PF), 87.3 +/- 1.8 (NF) (ns). Stimulation index (SI): 20 +/- 6.3 (FF), 80.2 +/- 28.2 (PF), 21.6 +/- 3.5 (NF) (ns) No correlation was observed between SI and any other parameter nor between SI and C-peptide levels. Islet mass significantly correlated with C-peptide levels at 6 and 12 months after transplantation for functioning grafts. CONCLUSIONS: Stringent product release criteria allow identification of islet preparations suitable for clinical transplantation. However, currently used parameters are not predictive of long-term graft function, indicating that further refined quality assessments including apoptosis and resistance to early inflammation, are required to assess the primary engrafted islet mass.